Operational Technology Services to Support Business Activities - Del Sale, Daniele (My University, 2021)
The operational technology (OT) environment is a vital part of several businesses around the world. While most of these businesses rely on the activities conducted there in order to generate revenue, it is not always correctly secured, and it is treated as a mere extension of the company's IT network. In this thesis it is described how OT-specific services were designed to protect the company business while, at the same time, keeping into consideration the needs of the people operating in the environment. It is also described how the design was implemented in practice, describing the technology and the entities involved. Finally, the use case definition and the testing phase is described to report what kind of problem arose only later and how they were approached to be solved. In short, this thesis follows the entire development of these services, starting from the very beginning until the present moment, meaning the successful conclusion of the testing phase and the start of the operational phase.
Keywords: OT, processes, cybersecurity, services, security, production